Genetic determinants of bone mass in adults. A twin study. - Pocock, N A (1987)
The relative importance of genetic factors in determining bone mass in different parts of the skeleton is poorly understood. Lumbar spine and proximal femur bone mineral density and forearm bone mineral content were measured by photon absorptiometry in 38 monozygotic and 27 dizygotic twin pairs. Bone mineral density was significantly more highly correlated in monozygotic than in dizygotic twins for the spine and proximal femur and in the forearm of premenopausal twin pairs, which is consistent with significant genetic contributions to bone mass at all these sites. The lesser genetic contribution to proximal femur and distal forearm bone mass compared with the spine suggests that environmental factors are of greater importance in the aetiology of osteopenia of the hip and wrist. This is the first demonstration of a genetic contribution to bone mass of the spine and proximal femur in adults and confirms similar findings of the forearm. Furthermore, bivariate analysis suggested that a single gene or set of genes determines bone mass at all sites.